Perceived organizational politics, turnover intention, and commitment in higher education institutions: the contingent role of Islamic work ethics - Abdi, Ahmed-Nor Mohamed; Mohamed, Mohamud Ahmed; Farah, Mohamed Ali (Frontiers in Education, 2025)
In higher education institutions, perceived organizational politics has been linked to adverse organizational outcomes. However, Islamic work ethics that include moral integrity, accountability, and fairness may act as a protective barrier against these detrimental consequences, especially in situations such as Somalia, where Islamic beliefs heavily influence professional behavior. Drawing on the Social Exchange and Conservation of Resources theories, this study explored the influence of perceived organizational politics on academic staff turnover intentions and professional commitment in private universities in Mogadishu, Somalia. Furthermore, this study examines the moderating role of Islamic work ethics in these associations. A quantitative online survey research design was used to collect data from 236 academic staff of private universities in Mogadishu, Somalia. We analyzed the data using SmartPLS version 4 to test the proposed hypotheses using Partial Least Square structural equation modeling (PLS-SEM). The results revealed that perceived organizational politics had a significant positive influence on academic staff’s turnover intention and a significant negative influence on their professional commitment. However, the results showed that the moderating effect of Islamic work ethics was negative but insignificant in the relationship between perceived organizational politics and both academic staff’s turnover intention and professional commitment. This study adds to the existing scholarship on organizational politics within higher education in post-war nations, especially in the Somali setting. This study provides new perspectives on the possible moderating influence of Islamic work ethics in reducing the adverse consequences of perceived organizational politics; however, it is limited.